The Ancient Silk Road And The New Silk Road Of The 21st Century : Comparative Study - Silva, Ray; Fatimah, Siti (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2025)
The world system consists of core, semi-periphery and periphery. Along the way, China experienced significant economic growth, attracting world attention. Since thousands of years ago until now there have been famous trade routes, namely the Ancient Silk Road and the New Silk Road of the 21st century which have brought China to become the core of the world. This research aims to find out the comparison between the Ancient Silk Road and the New Silk Road of the 21st century using historical research methods. The results of this research show differences and similarities between the Ancient Silk Road and the New Silk Road of the 21st century in terms of the commodities used for activities, the Silk Road travel routes, the regions involved, developments in transportation technology and the impact on the world system.